Synthesis and Characterization of Polyvinyl Alcohol (PVA) Nanofiber Membranes with Annonamuricata and Terminalia catappa Leaf Extract - Fitria, Silfiyana; Almafie, Muhammad Rama; Alfikro, Ihsan; Monado, Fiber; Sriyanti, Ida; Royani, Idha (Science and Technology Indonesia, 2025)
Polyvinyl alcohol (PVA) is hydrophilic, flexible, elastic, and environmentally friendly, leading to the wide use as a binder in nanofiber matrices. The nanofibers of PVA are frequently combined with extract possessing antibacterial properties for characterization. Therefore, this study aimed to produce PVA nanofibers incorporating soursop leaf extract (ALE) and catappa leaf extract (CLE) using electrospinning for the investigation of the physicochemical, mechanical, and antibacterial properties. Electron microscopy showed that the electrospun nanofibers had a yellowish-brown surface with diameters ranging from 962 nm to 1323 nm. Fourier Transform Infrared (FTIR) analysis revealed the presence of functional groups interacting through hydrogen bonding, leading to a shift in wavenumbers. The tensile strength of PAC-1, PAC-2, and PAC-3 nanofibers decreased from 8.46 MPa to 4.27 MPa, followed by a reduction in Young’s modulus from 20.2 MPa to 0.89 MPa. The effect of extract concentration on the reduction in tensile strength and Young’s modulus was related to aggregation in certain areas of the nanofibers and weakened intermolecular polymer interactions. Pure extract had strong antibacterial activity and nanofiber membranes had moderate activity with inhibition zones ranging from 12.3 to 16.8 mm and 8.0 to 14.4 mm, respectively. The results showed that the produced fibers could be used in the biomedical field for wound dressings and filtration, as well as in textiles.